A modified technique for reducing the duration of ischemic time of the heart and myocardial reperfusion in multivalve correction combined with coronary grafting - P.M. Semeniv (Кардіохірургія та інтервенційна кардіологія)
The aim – to develop and put into practice a method of reducing the ischemic time of the heart during long-term cardiac surgery interventions. Materials and methods. A modified technique of coronary artery bypass grafting has been developed for combined operations that require a long time to clamp the aorta. The results of simultaneous correction of valve defects and coronary artery bypass grafting in 15 patients were analyzed. At the first stage, off-pump coronary artery bypass grafting was performed, followed by correction of valvular lesions. Results. The used technique requires more time to perform and is technically more difficult, but it allows to significantly reduce the ischemic time of the myocardium, which in turn will prevent heart failure and postoperative complications. Conclusions. The application of the technique proposed in the experiment has significant advantages in terms of the duration of artificial blood circulation and the ischemic time of the heart, which favorably affects its performance.